2003
DOI: 10.1002/anie.200250400
|View full text |Cite
|
Sign up to set email alerts
|

The First Isolable 2‐Silenolate

Abstract: Reversed SiC bond polarity is displayed by the first isolable 2‐silenolate. [(TMS)2SiC(O)tBu]−K+, which is thermally stable at room temperature and structurally characterized by X‐ray crystallography, contains a CO double bond and a SiC single bond with a strongly pyramidal Si center. These results in combination with NMR spectroscopic and atomic‐charge data indicate that resonance structure II domincates the electronic structure. TMS=trimethylsilyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…The 13 C shift of 268.3 ppm revealed a very deshielded central C atom, and the 29 Si shift of −64.5 ppm for the central Si atom indicated that is was very shielded. This 29 Si shift is similar to that of Kira's 4-silatriafulvene (−71.9 ppm [58]) and those of the silenolates prepared by Ohshita, Ishikawa, and Ottosson (−79 to −60 ppm [72,73]). …”
Section: -Silaallenessupporting
confidence: 71%
See 2 more Smart Citations
“…The 13 C shift of 268.3 ppm revealed a very deshielded central C atom, and the 29 Si shift of −64.5 ppm for the central Si atom indicated that is was very shielded. This 29 Si shift is similar to that of Kira's 4-silatriafulvene (−71.9 ppm [58]) and those of the silenolates prepared by Ohshita, Ishikawa, and Ottosson (−79 to −60 ppm [72,73]). …”
Section: -Silaallenessupporting
confidence: 71%
“…However, there is experimental evidence for a reduced dimerization aptitude of reverse polarized silenes. In the thermolytic formation of the transient 2-amino-2-siloxysilenes (75a-75c, Scheme 22) very little dimer formation was observed [8], and potassium silenolates revealed no tendency for dimerization [73]. Formation of dimers from lithium silenolates was suggested but not proven [72,121].…”
Section: Dimerization Aptitudementioning
confidence: 95%
See 1 more Smart Citation
“…[15] TheS i1ÀB1 bond in [2] À [1.859(2) ]i s similar in length to that in the neutral borasilene A [1.8379-(17) ]a nd considerably shorter than that in borasileneacetylide adduct A' ' [1.933 (3) ]. [16] TheB1 ÀCl1 bond in [2] À [1.879 (2) ]issignificantly longer than that in precursor 4 [1.7751 (17) ], which suggests that the electron donation from the chloride to the boron atom is weaker than in 4.T hese structural parameters show that the Si = Bb ond in [2] À exhibits double-bond character, with little contribution from as ilyl anion (R H 2 Si À ÀBMesCl) resonance structure. [16] TheB1 ÀCl1 bond in [2] À [1.879 (2) ]issignificantly longer than that in precursor 4 [1.7751 (17) ], which suggests that the electron donation from the chloride to the boron atom is weaker than in 4.T hese structural parameters show that the Si = Bb ond in [2] À exhibits double-bond character, with little contribution from as ilyl anion (R H 2 Si À ÀBMesCl) resonance structure.…”
mentioning
confidence: 99%
“…Following the results described by Ottosson and coworkers for the generation of stable silenolates, [15] we reacted 2 with equimolar amounts of KO t Bu. As expected, the base was fully consumed for the abstraction of one SiMe 3 group to give monosilenolate 4.However, 4 was never isolated, even at low temperatures;instead, it reacted further in the proposed sila-aldol reaction.…”
mentioning
confidence: 99%